Koridor Hak Asasi Manusia dalam Hukum Acara Pidana Indonesia: Sebuah Retrospeksi atas Nilai-nilai Politik Kenegaraan dalam Pembangunan Hukum di Indonesia - Karim, Sawir (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2003)
This article focuses on how state set up limitations and corridors of human rights action through a regulation in criminal law and court law in Indonesia. The writing method particularly provides stressing on steps of Indonesian court law, which is consists of arresting, identification as well as confiscation of the criminal cases. Although it is accepted thatÂ several steps in court and criminal law provide a limit and a restriction of human rights, actually by the law number 14 of 1970 about the Basic Authorities of the Court, the value of human rught is guarantee by many principles in the legal system such as a similar action of every persons, every official act should based on written documents, a rehabilitation and compensation for missarresting by state, et cetera. In conclusion, state authority by Indonesia court and criminal law may be functioned as a tool of social engineering. Â Kata Kunci: Pembatasan HAM, Hukum Acara Pidana